Core and Peripheral Voters: Predictors of Turnout Across Three Types of Elections. (May 2019) - Bhatti, Yosef; Dahlgaard, Jens Olav; Hansen, Jonas Hedegaard; Hansen, Kasper M
Citizens who abstain from voting in consecutive elections and inequality in turnout in democratic elections constitute a challenge to the legitimacy of democracy. Applying the law of dispersion, which stipulates higher levels of turnout and higher levels of equality in turnout are positively related, we study turnout patterns across different types of elections in Denmark, a high-turnout European context. Across three different elections with turnout rates from 56.3% to 85.9%, we use a rich, nationwide panel dataset of 2.1 million citizens with validated turnout and high-quality sociodemographic variables. A total of 9% of the citizens are abstainers in the three consecutive elections, and these are disproportionately male, of non-Western ethnic background, with little education, and with low income. The law of dispersion finds support as inequalities in turnout increase when turnout decreases and vice versa. Furthermore, municipalities with lower turnout have higher inequalities in participation than high-turnout municipalities in local elections.